The effects of modified sini decoction on liver injury and regeneration in acute liver failure induced by d-galactosamine in rats. (23rd February 2015) - Luo, Jianxing; Zhang, Yang; Hu, Xiaoyu; Zhong, Sen; Chen, Guo; Wang, Yanyan; Lin, Wu; Yi, Cheng; Zhu, Hong
Abstract: Ethnopharmacological relevance: Modified sini decoction (MSND) is a well-known traditional Chinese medical formula that has been used to treat cardiovascular and liver diseases for many years. We investigated the effects of MSND on acute liver failure and identified the possible mechanisms of these effects. Material and methods: Acute liver failure was induced by intraperitoneal injection ofd -galactosamine (d -GalN) into specific pathogen-free male Wistar rats. Next, the rats were treated with Stronger Neo-Minophagen C and MSND via gavage. Biochemical parameters, histological changes in the liver, the survival of rats and the mRNA levels of toll-like receptor 4 (TLR4), nuclear factor kappa B (NF-κB), high mobility group box 1 (HMGB1) caspase-3 and proliferating cell nuclear antigen (PCNA) were analyzed. Results: MSND prolonged the survival times of the acute liver failure rats. The biochemical parameters were improved, and necrosis in the liver tissues was reduced by both Stronger Neo-Minophagen C (SNMC) and MSND, but MSND induced greater effects. The mRNA expressions of HMGB1, TLR4, NF-κB, and Caspase-3 were remarkably decreased, and the expression of PCNA was remarkably increased by SNMC and MSND, and the effects of MSND were greater. Conclusions: MSND protected the liver and increased the survival rate of acute liver failure rats. These effects were likely mediated by the inhibitions of the inflammatory reaction and apoptosis and the promotion of liver tissue regeneration. Graphical abstract: Modified sini decoction (MSND) improved the liver function, reduced the hepatic pathological damage and prolonged the survival time of rats with ALF induced byd -GalN. MSND was more effective than SNMC. These effects were most likely mediated by the inhibition of the HMGB1/TLR4/NF-κB pathway, the downregulation of the mRNA expression of Caspase-3 and the upregulation of PCNA expression.